Video head impulse test in bilateral vestibulopathy - Elsherif,Mayada (2022)
Abstract Introduction: Bilateral vestibulopathy is a rare chronic condition with multiple etiologies. Bilateral vestibulopathy is characterized mainly by unsteadiness when walking or standing, which worsens in darkness, as well as oscillopsia. The degree of handicap caused by bilateral vestibulopathy is variable and remains controversial. Objectives: To determine the value of the video Head Impulse Test in quantifying vestibular deficit and to establish its impact on the quality of life. Methods: Twenty patients (mean age, 41.9 years; range 14-80 years) fulfilling the recent Barany criteria of bilateral vestibulopathy, responded to the Situational Vertigo Questionnaire and underwent vestibular examination including fixation, positional tests, oculomotor test battery and video head impulse test. Results: The relation between each of the video head impulse test parameters and the scores from the questionnaire were statistically analyzed. We observed that patients with covert saccades on the video head impulse test were more likely to have a better quality of life than those with both covert and overt saccades, regardless of the vestibulo-ocular reflex gain in each semicircular canal. The presence of covert saccades was found to be associated with an improved quality of life regardless of the severity of vestibule ocular reflex-deficit. Our conclusion was that vestibule ocular reflex gain, measured by video head impulse test, does not quantify the severity of affection of quality of life in patients with bilateral vestibulopathy. Conclusion: Covert saccades are strategies aiming at minimizing the blurring of vision during head movement, that is an adaptive mechanism that improves quality of life. Therefore, we recommend that video head impulse test should be a part of the routine diagnostic workup of bilateral vestibulopathy.